Mislabelling Absolute Neurological Illnesses as Conversion Disorder - Shoja Shafti, Saeed (International Journal of Psychosocial Rehabilitation, 2017)
The incidence of medical mistakes in primary care is not rare and the probability of faults producing grave detriment is great. Medical negligence is a ‘tort’, or ‘civil wrong’. It is a ‘wrong’ resulting from a doctor’s carelessness. Simply put, negligence means failing to do something that should have been done as defined by current medical practice or doing something that a physician with a duty to care for the patient should not have done. Whereas about one percent of hospital admissions result in an adversative event due to negligence, faults are probably much more common, because these studies detect only errors that led to assessable adversative events occurring soon after the mistakes. Moreover, though after heart disease and cancer, medical mistake is the 3rd important reason of death in the USA, maybe the real problem in medical faults is not bad persons in health care; rather it is that good individuals are working in corrupt systems. Poor communiqué , blurred lines of power of doctors, nurses, and other care providers, incoherent recording systems, differences in healthcare provider teaching and practice , failure to recognize the frequency and significance of medical mistakes, overestimation of insufficient data, sleep deficiency and night shifts, doctor’s depression, fatigue, and burnout , unfamiliar settings, diverse patients, and time pressures have been accounted as vital causes of medical error. In the following article, some proven neurologic cases, which have been diagnosed in the beginning by at least one neurologist as conversion disorder and referred to psychiatric facilities, have been described. This article tries to give the reader an awareness regarding the aforesaid dilemma, in the ground of psychological medicine.